Analisis Tingkat Kesejahteraan Masyarakat Sekitar Industri Tebu PT Jhonlin Batu Mandiri Menggunakan Pendekatan Maqashid Syari’ah : (Studi di Desa Watu-Watu Kec. Lantari Jaya Kab. Bombana) - Toar, Alfian; B, Jumiati; Wahid Mongkito, Abdul (MADINAH, 2021)
This study aims to find out how the welfare conditions of the people of Watu-watu Village use the Maqashid Syari'ah approach, and the role of the PT industry. Jhonlin Batu Mandiri in improving the welfare of the people of Watu-watu Village according to the principles of Maqashid Syariah. This type of research uses a qualitative descriptive approach by analyzing, describing, and at the same time summarizing various conditions, situations, various data collected in the form of interviews and observations of problems that occur in the field with using data collection techniques Interview, Observation, and Documentation. The results of the study show that the welfare conditions of the people of Watu-watu Village using the Maqashid Syari'ah Approach fulfill five main elements, namely protecting religion (Hifdzu din), protecting the soul (Hifdzu Nafs), protecting the mind (Hifdzu Aql), protecting offspring (Hifdzu Nasl), guarding property (Hifdzu Maal). Meanwhile, the role of the industrial presence of PT. Jhonlin Batu Mandiri in Watu-Watu Village, Lantari Jaya District, Bombana Regency has provided a source of basic and additional income for the community, this is because PT. Jhonlin Batu Mandiri opened job vacancies and recruited some of the people of Watu-watu Village as employees so that the surrounding community experienced an increase in the economy in a better direction and the community was able to support their needs. In addition to increasing welfare in terms of food, clothing, shelter and health, the surrounding community can also feel well-being on the spiritual side so that the presence of PT. Jhonlin Batu Mandiri, Watu-Watu Village, Lantari Jaya District, Bombana Regency is in accordance with the principles of Maqashid Syari'ah in this case the industry not only increases welfare in the world but supports welfare in the afterlife.